The longitudinal impact of division-wide implementation of an enhanced recovery after thoracic surgery programme. (24th November 2021) - Thompson, Calvin; Mattice, Amanda M S; Al Lawati, Yaseen; Seyednejad, Nazgol; Lee, Alex; Maziak, Donna E; Gilbert, Sebastian; Sundaresan, Sudhir; Villeneuve, James; Shamji, Farid; Brehaut, Jamie; Ramsay, Tim; et al.
Abstract: OBJECTIVES: Data regarding enhanced recovery after thoracic surgery (ERATS) are sparse and inconsistent. This study aims to evaluate the effects of implementing an enhanced ERATS programme on postoperative outcomes, patient experience and quality of life (QOL). METHODS: We conducted a prospective, longitudinal study evaluating 9 months before (pre-ERATS) and 9 months after (post-ERATS) a 3-month implementation of an ERATS programme in a single academic tertiary care centre. All patients undergoing major thoracic surgeries were included. The primary outcomes included length of stay (LOS), adverse events (AEs), 6-min walk test scores at 4 weeks, 30-day emergency room visits (without admission) and 30-day readmissions. The process-of-care outcomes included time to 'out-of-bed', independent ambulation, successful fluid intake, last chest tube removal and removal of urinary catheter. Perioperative anaesthesia-related outcomes were examined as well as patient experience and QOL scores. RESULTS: The pre-ERATS group ( n  = 352 patients) and post-ERATS group ( n  = 352) demonstrated no differences in demographics. Post-ERATS patients had improved LOS (4.7 vs 6.2 days, P  < 0.02), 6-min walk test scores (402 vs 371 m, P  < 0.05) and 30-day emergency room visits (13.7% vs 21.6%, P  = 0.03) with no differences in AEs and 30-day readmissions. Patients experienced shorter mean time to 'out-of-bed', independent ambulation, successful fluid intake, last chest tube removal and urinary catheter removal. There were no differences in postoperative analgesia administration, patient satisfaction and QOL scores. CONCLUSIONS: ERATS implementation was associated with improved LOS, expedited feeding, ambulation and chest tube removal, without increasing AEs or readmissions, while maintaining a high level of patient satisfaction and QOL. Abstract : Surgical interventions for thoracic cancer are among the most challenging procedures, particularly for patients with limited physiological reserve [1, 2].